2006
DOI: 10.1152/japplphysiol.01303.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eccentric exercise on position sense at the human forearm in different postures

Abstract: Effect of eccentric exercise on position sense at the human forearm in different postures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 24 publications
3
45
0
1
Order By: Relevance
“…Walsh et al (2006) tested the ability to match forearm position before and after a repetitive eccentric elbow extension movement at 30 % of maximum voluntary contraction (MVC) and found that the task arm had systematically more elbow flexion than the reference arm. In contrast, repetitive 10-s isometric elbow flexor contractions at 30 % MVC and repetitive eccentric flexion and extension movements performed to fatigue lead to position errors in the direction of extension (Tsay et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Walsh et al (2006) tested the ability to match forearm position before and after a repetitive eccentric elbow extension movement at 30 % of maximum voluntary contraction (MVC) and found that the task arm had systematically more elbow flexion than the reference arm. In contrast, repetitive 10-s isometric elbow flexor contractions at 30 % MVC and repetitive eccentric flexion and extension movements performed to fatigue lead to position errors in the direction of extension (Tsay et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, we need to emphasize again that our protocol was relatively mild in intensity. Interestingly, several studies have reported errors in the matching of force and position with elbow flexors immediately after eccentric exercise (34,35,45). Such errors point to a disturbance in proprioception and indicate a change in motor control during submaximal force tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence suggests that subjects are not as accurate in forearm matching in the horizontal plane compared with the vertical plane. 77 Furthermore, in the horizontal plane, muscle fatigue does not introduce additional position errors. This suggests that an effort sensation, as such, does not contain positional information for movements in the horizontal plane.…”
Section: Position Sensementioning
confidence: 99%
“…This suggests that an effort sensation, as such, does not contain positional information for movements in the horizontal plane. 77 Recent experiments on position sense with loaded arms suggest that a centrally generated signal does manifest itself in the horizontal plane, but only if the load is moved by the subject (Ansems, Allen, and Proske, unpublished observations).…”
Section: Position Sensementioning
confidence: 99%